Persepsi Pengunjung Domestik Terhadap Wisata Entertainment di Daya Tarik Wisata Kawasan Luar Pura Uluwatu - Tjampan, Kesya Marcella; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2020)
The strategy forming tourist attraction to attract repeating guest is by developing entertainment tourism which offers sense of pleasure, satisfaction, and valuable experience. Uluwatu Kecak Fire Dance in Outer Area Uluwatu Temple was recognized as the most famous entertainment forms by domestic visitors. This aim of study is to identifying characteristics and measuring perception of domestic visitors to Uluwatu Kecak Fire Dance based on seven operational dimensions of entertainment tourism (Learning, Enjoyment, Escape, Refreshment, Novelty, Involvement, and Local Culture). The research used qualitative method with data collection techniques are questionnaire (number of samples were 65 respondents) and literature study. The data analysis technique used descriptive statistical analysis with continuum lines. The results showed that the perception of 65 domestic visitors for entertainment tourism in Uluwatu Temple were strongly agreed on Learning (277.5) and Enjoyment (285). While perception that were agreed are Escape (227), Refreshment (248.5), Novelty (259.25), Involvement (266), and Local Culture (272.33). In determining the dominant indicators of each dimension of entertainment tourism, the author uses the highest frequency capacity value. The three dimensions with highest average value are Enjoyment (285), Learning (277.5), and Local Culture (272.33). The administrator Outer Area Uluwatu Temple emphasize strategies that can maintain the three dimensions of entertainment tourism that have a dominant value, which is the Enjoyment dimension, Learning dimension, and the Local Culture dimension.   Keyword : Visitor Perception, Socio-demographic Characteristics, Entertainment Tourism, Domestic Visitors